Preparation method of high-strength corrosion-resistant fine-grain titanium alloy plate

By adding rare earth elements to TC4 titanium alloys and using asynchronous rolling and multi -stage solid solution treatment, high -density and multi -level wrong structures are formed, solving problems in the existing technology. The effect of high strength and corrosion resistance is achieved.

CN119368741AActive Publication Date: 2025-01-28KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411539766.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The prior art has problems such as long production cycle, high cost and difficulty in post-treatment in improving the surface strength and corrosion resistance of TC4 titanium alloys, and it is easy to add impurity elements to affect the alloy structure and morphology.

Method used

Add rare earth elements through the gas atomization method, such as LA, CE, PR, and YB, and combined with asynchronous rolling, multi -stage solid solution treatment, quenching and timeliness, forming high -density and multi -level error structures, improving the precipitated phase and matrix body Combining strength.

Benefits of technology

It significantly improves the strength and corrosion resistance of titanium alloy plates, reduces costs, reduces the consumption of specific rare earth resources, and expands the application of titanium alloy in aerospace, automobiles and marine engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368741A_ABST
    Figure CN119368741A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength corrosion-resistant fine-grain titanium alloy plate, and belongs to the technical field of preparation of high-strength corrosion-resistant materials. The high-strength corrosion-resistant TC4 titanium alloy is prepared from the following components in percentage by mass: 5.5 to 6.5 percent of Al, 3.7 to 4.2 percent of V, 0.8 to 1.2 percent of La, 0.03 to 0.05 percent of Ce, 0.02 to 0.04 percent of Pr, 0.01 to 0.02 percent of Yb and the balance of Ti and trace impurity elements. The preparation method of the finished product material comprises the processes of gas atomization treatment, pressing, sintering, pre-aging treatment, asynchronous cold rolling treatment, multi-stage solution treatment, quenching and artificial aging treatment. The strength, the toughness and the corrosion resistance of the finally obtained high-strength corrosion-resistant fine-grain titanium alloy plate are improved; the workpiece can be used for aerospace or ocean engineering, and has a very good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-strength, corrosion-resistant, fine-grained titanium alloy plate, and belongs to the technical field of preparing high-strength, high-toughness, corrosion-resistant titanium alloys. Background Art

[0002] TC4 titanium alloy, also known as Ti-6Al-4V, is a titanium alloy widely used in aerospace, automobile, chemical, shipbuilding and other fields. It has high strength, good corrosion resistance, low density and excellent comprehensive mechanical properties. The manufacturing and processing technology of TC4 titanium alloy has always been a hot topic in materials science research.

[0003] Chinese invention patent CN118531342A introduces a process for improving the surface strength and corrosion resistance of metal materials. The process mainly uses surface modification technology to nitridize the surface of TC4 titanium alloy material to form a nitrided layer, thereby improving the corrosion resistance of the material to a certain extent. However, due to the long production cycle, high cost and difficult post-processing of nitriding treatment, it is not conducive to actual production application.

[0004] Chinese invention patent CN118291810A introduces a new type of high-strength corrosion-resistant titanium alloy and its preparation method, in which other elements are added by alloy smelting. This process easily adds other impurity elements, thereby affecting the microstructure of the alloy.

[0005] Therefore, it is necessary to provide a method for preparing a high-strength, corrosion-resistant, fine-grained titanium alloy plate, to strengthen the strength of the surface of the titanium alloy plate, and to improve the protective effect and duration of the surface corrosion resistance. Summary of the invention

[0006] In order to overcome the problems in the background technology, the present invention adds rare earth elements through aerosolization, so that the synthesized sample powder has a higher purity and avoids the influence of other impurity elements on the microstructure and performance. Then, it combines asynchronous rolling, multi-stage solution treatment, quenching and aging treatment to form a high-density multi-level dislocation structure, so that the solute atoms are evenly distributed, and the bonding strength between the precipitated phase and the matrix is ​​improved, which greatly improves the strength and corrosion resistance of the plate, and further expands the application of titanium alloy materials in aerospace, automobile, marine engineering and other fields.

[0007] In order to achieve the above object, the present invention is implemented by the following technical scheme: by adding rare earth elements (La, Ce, Pr and Yb) and adopting inert gas atomization, pressing, sintering, preheating treatment, asynchronous rolling, high temperature solution, quenching, aging treatment and other processes to obtain the required strong and tough wear-resistant texture, specifically including the following steps:

[0008] (1) Gas atomization treatment: The prepared rare earth raw materials and TC4 alloy raw materials are mixed by inert gas atomization treatment.

[0009] (2) The prepared titanium alloy powder is subjected to pressing and sintering, pre-aging treatment, asynchronous cold rolling treatment, solution treatment, and quenching treatment in sequence.

[0010] (3) The samples were then artificially aged at a temperature of 400-420°C for 4 h and then air-cooled to room temperature.

[0011] Furthermore, the titanium alloy of the present invention mainly comprises 5.5-6.5% Al, 3.7-4.2% V, 0.8-1.2% La, 0.03-0.05% Ce, 0.02-0.04% Pr, 0.01-0.02% Yb, and the remainder is Ti and some inevitable impurity elements; the present invention can refine the grains and reduce defects in the processing process in the later treatment by adding trace rare earth elements at the same time, thereby improving the strength of the alloy.

[0012] Preferably, the gas atomization treatment conditions of the present invention are as follows: the induction power reaches 60kW, the atomization pressure is 6.0MPa; argon is introduced into the inert gas to prevent the titanium alloy from reacting with oxygen at high temperature, the melting temperature is 1750-1800°C, the atomization pressure is about 6.0MPa, and the gas flow rate is 60-80m 3 / h.

[0013] Preferably, in the pressing and sintering of the present invention, the titanium alloy powder is pressed into a plate and then sintered, the sintering temperature is 1150-1300° C., and the duration is 2 hours.

[0014] Preferably, the parameters of the pre-annealing treatment of the present invention are: 300-350° C. for 2 hours.

[0015] Preferably, the conditions for the asynchronous cold rolling treatment of the present invention are: during asynchronous cold rolling, the speed ratio of the upper and lower rollers is 1.2, the total pressing amount of the sample is 50%, the number of pressing times is 10 times, and the pressing amount each time is not less than 5%.

[0016] Preferably, in step (2) of the present invention, a multi-stage solution treatment is performed, wherein the solution temperature of the first stage is 850°C, and the insulation time is 2 hours; the solution temperature of the second stage is 900°C, and the insulation time is 2 hours; the solution temperature of the third stage is 950°C, and the insulation time is 2 hours.

[0017] Preferably, in the artificial aging treatment process in step (5) of the present invention, the aging temperature is 400-420° C. and the insulation time is 4 hours.

[0018] Beneficial effects of the present invention:

[0019] (1) The present invention reduces the dependence on and the amount of addition of a single rare earth element by adding a reasonable ratio of multiple rare earth elements, thereby reducing costs and reducing the consumption of specific rare earth resources; there is a synergistic effect between different rare earth elements. Through appropriate heat treatment processes, the strengthening effect of rare earth elements can be further exerted, promoting the formation of precipitation phases, thereby improving the strength and corrosion resistance of the alloy.

[0020] (2) Through solution aging treatment, rare earth elements are stimulated to improve the interfacial bonding strength between the precipitated phase and the matrix titanium, and the combination of Ce, Pr and Yb can more effectively enhance this interfacial bonding; Ce and La can combine with oxygen to form stable oxides, reduce oxidation in the alloy, and improve the corrosion resistance of the alloy; the co-addition of La, Ce and Yb rare earth elements can more effectively consume harmful solute atoms during the solution process, thereby reducing grain boundary embrittlement and improving the strength of the alloy.

[0021] (3) In the present invention, the asynchronous cold rolling method is adopted, which can reduce the deformation resistance of the material and improve the deformation degree compared with the ordinary cold rolling; at the same time, it can promote the formation of twin boundaries in the material and improve the plasticity and toughness of the titanium alloy.

[0022] (4) The multi-stage solution treatment used in the present invention allows the asynchronously cold rolled alloy to be kept at a temperature of 850°C, so that most of the eutectic phase is dissolved back into the matrix. When the temperature reaches 900°C, the eutectic structure begins to show anisotropy. Finally, when the temperature reaches 950°C, the grains are recrystallized, and the grains are uniformly refined to obtain a fine equiaxed α phase + β phase structure, thereby greatly improving the strength and corrosion resistance of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a flow chart of the present invention.

[0024] Figure 2 It is a schematic diagram of part of the production process of the high-strength, corrosion-resistant, fine-grained titanium alloy plate of the present invention. Specific implementation plan

[0025] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the contents.

[0026] Example 1

[0027] The chemical composition of the high-strength, corrosion-resistant, fine-grained titanium alloy plate implemented in the present invention is shown in Table 1.

[0028] Table 1 Chemical composition (wt%) of high strength corrosion resistant fine-grained titanium alloy plate of a specific embodiment of the present invention

[0029] A1 V La Ce Pr Yb margin 5.7 3.8 1.0 0.05 0.04 0.02 Ti and inevitable impurities

[0030] The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment specifically comprises the following steps:

[0031] (1) The alloy was subjected to gas atomization treatment according to the composition in Table 1. The prepared rare earth raw materials and titanium alloy raw materials were subjected to gas atomization treatment and mixed separately. The gas flow rate was 60m 3 / h, the gas pressure is 1.6MPa, the melting temperature is 1800℃, and then the two are fully mixed during atomization to form fine spherical powder particles under the atmosphere of inert gas nitrogen.

[0032] (2) The alloy powder obtained in step (1) was mixed evenly and pressed into a rectangular billet of 50 mm × 50 mm × 20 mm by a hydraulic press at a pressure of 300 MPa and a holding time of 5 min.

[0033] (3) The blank obtained in step (2) is placed in a vacuum sintering furnace for heating and sintering. The blank is heated to 1200° C. at a rate of 60° C. / min and sintered for 2 h to obtain the desired sample.

[0034] (4) The alloy sample in step (3) is subjected to a pre-annealing treatment at 300° C. for 2 h to reduce the internal stress, and an asynchronous cold rolling treatment is performed, the speed ratio of the upper and lower rollers is 1.2, the total pressing amount of the sample is 50%, the number of pressing times is 10 times, and the pressing amount each time is not less than 5%.

[0035] (5) The alloy sample after asynchronous rolling in step (4) is subjected to a multi-stage solution treatment, wherein the first stage solution temperature is 850°C and the insulation time is 2 hours; the second stage solution temperature is 900°C and the insulation time is 2 hours; the third stage solution temperature is 950°C and the insulation time is 2 hours; followed by water cooling quenching for 5 minutes; and finally artificial aging treatment is performed at an aging temperature of 400°C and the insulation time is 4 hours. The yield strength, tensile strength and elongation of the alloy are measured to be 970.2 MPa, 1175.4 MPa and 17.7%.

[0036] Example 2

[0037] The chemical composition of the high-strength, corrosion-resistant, fine-grained titanium alloy plate implemented in the present invention is shown in Table 1.

[0038] Table 2 Chemical composition (wt%) of high strength corrosion resistant fine grain titanium alloy plate of the specific embodiment of the present invention

[0039] Al V La Ce Pr Yb margin 6.2 4.1 1.2 0.03 0.02 0.01 Ti and inevitable impurities

[0040] The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment specifically comprises the following steps:

[0041] (1) The alloy was subjected to gas atomization treatment according to the composition in Table 2. The prepared rare earth raw materials and titanium alloy raw materials were subjected to gas atomization treatment and mixed separately. The gas flow rate was 80m 3 / h, the gas pressure is 1.6MPa, the melting temperature is 1800℃, and then the two are fully mixed during atomization to form fine spherical powder particles under the atmosphere of inert gas nitrogen.

[0042] (2) The alloy powder obtained in step (1) was mixed evenly and pressed into a rectangular billet of 50 mm × 50 mm × 20 mm by a hydraulic press at a pressure of 300 MPa and a holding time of 5 min.

[0043] (3) The blank obtained in step (2) is placed in a vacuum sintering furnace for heating and sintering. The blank is heated to 1150° C. at a rate of 60° C. / min and sintered for 2 h to obtain the desired sample.

[0044] (4) The alloy sample in step (3) is subjected to a pre-annealing treatment at 340° C. for 2 h to reduce the internal stress, and an asynchronous cold rolling treatment is performed, the speed ratio of the upper and lower rollers is 1.2, the total pressing amount of the sample is 50%, the number of pressing times is 10 times, and the pressing amount each time is not less than 5%.

[0045] (5) The alloy sample after asynchronous rolling in step (4) was subjected to a multi-stage solution treatment, wherein the first stage solution temperature was 850°C and the insulation time was 2 hours; the second stage solution temperature was 900°C and the insulation time was 2 hours; the third stage solution temperature was 950°C and the insulation time was 2 hours; followed by water cooling quenching for 5 minutes; and finally artificial aging treatment was performed at an aging temperature of 420°C and the insulation time was 4 hours. The yield strength, tensile strength and elongation of the alloy were measured to be 953.2 MPa, 1146.7 MPa and 15.4%.

[0046] Example 3

[0047] The chemical composition of the high-strength, corrosion-resistant, fine-grained titanium alloy plate implemented in the present invention is shown in Table 3.

[0048] Table 3 Chemical composition (wt%) of high strength corrosion resistant fine-grained titanium alloy plate of the specific embodiment of the present invention

[0049] Al V La Ce Pr Yb margin 6.5 3.7 0.8 0.04 0.03 0.02 Ti and inevitable impurities

[0050] The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment specifically comprises the following steps:

[0051] (1) The alloy was subjected to gas atomization treatment according to the composition in Table 3. The prepared rare earth raw materials and titanium alloy raw materials were subjected to gas atomization treatment and mixed separately. The gas flow rate was 70m 3 / h, the gas pressure is 1.6MPa, the melting temperature is 1750℃, and then the two are fully mixed during atomization to form fine spherical powder particles under the atmosphere of inert gas nitrogen.

[0052] (2) The alloy powder obtained in step (1) was mixed evenly and pressed into a rectangular billet of 50 mm × 50 mm × 20 mm by a hydraulic press at a pressure of 300 MPa and a holding time of 5 min.

[0053] (3) The blank obtained in step (2) is placed in a vacuum sintering furnace for heating and sintering. The blank is heated to 1250° C. at a rate of 60° C. / min and sintered for 2 h to obtain the desired sample.

[0054] (4) The alloy sample in step (3) is subjected to a pre-annealing treatment at 350° C. for 2 h to reduce the internal stress, and an asynchronous cold rolling treatment is performed, wherein the speed ratio of the upper and lower rollers is 1.2, the total pressing amount of the sample is 50%, the number of pressing times is 10 times, and the pressing amount each time is not less than 5%.

[0055] (5) The alloy sample after asynchronous rolling in step (4) was subjected to a multi-stage solution treatment, wherein the first stage solution temperature was 850°C and the insulation time was 2 hours; the second stage solution temperature was 900°C and the insulation time was 2 hours; the third stage solution temperature was 950°C and the insulation time was 2 hours, followed by water cooling quenching for 5 minutes; finally, artificial aging treatment was performed, the aging temperature was 410°C and the insulation time was 4 hours; the yield strength of the alloy was measured to be 967.8 MPa, the tensile strength was 1166.8 MPa, and the elongation was 16.1%.

[0056] Comparative Example 1

[0057] The heat treatment process for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment is the same as that in Embodiment 1, except that no rare earth elements (La, Ce, Pr and Yb) are added.

[0058] The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment specifically comprises the following steps:

[0059] (1) The TC4 alloy plate sample was pre-annealed at 300°C for 2 h to reduce the internal stress and improve the toughness. The sample was subjected to asynchronous cold rolling. The speed ratio of the upper and lower rollers was 1.2. The total pressing amount of the sample was 50%. The number of pressing times was 10 times, and the pressing amount each time was not less than 5%.

[0060] (2) The alloy sample after asynchronous rolling in step (1) was subjected to solution treatment, a multi-stage solution treatment, the first stage solution temperature was 850°C, the insulation time was 2 hours; the second stage solution temperature was 900°C, the insulation time was 2 hours; the third stage solution temperature was 950°C, the insulation time was 2 hours; then water cooling quenching, time 5min; finally artificial aging treatment, aging temperature was 400°C, insulation time was 4h. The yield strength of the alloy was measured to be 876.4MPa, the tensile strength was 945.6MPa, and the elongation was 10.4%.

[0061] By comparison, it can be seen that the strength of titanium alloy has dropped significantly. The reason may be that the solid solution of rare earth elements in the alloy can increase the resistance to dislocation movement, thereby increasing the strength of the material. When rare earth elements are not added, this solid solution strengthening effect may be weakened.

[0062] Comparative Example 2

[0063] The heat treatment process for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment is the same as that in Embodiment 1, except that only La is added as a rare earth element.

[0064] The yield strength of the alloy was measured to be 926.5 MPa, the tensile strength was 987.6 MPa, and the elongation was 11.6%.

[0065] By comparison, it can be seen that the yield strength and tensile strength of the alloy are significantly reduced compared with Example 1. The reason is that the single addition of La may lead to the formation of some unfavorable precipitation phases, causing stress concentration and reducing the plasticity of the alloy.

[0066] Comparative Example 3

[0067] The heat treatment process for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment is the same as that in Embodiment 1, except that only Ce is added as the rare earth element.

[0068] The yield strength of the alloy was measured to be 916.2 MPa, the tensile strength was 965.3 MPa, and the elongation was 13.9%.

[0069] By comparison, it can be seen that the Ce element has a small effect on improving the strength of the alloy. The reason is that the solid solubility of the Ce element in the alloy is usually low, and they tend to form compounds or aggregate near the grain boundaries, thereby reducing the strength of the alloy.

[0070] Comparative Example 4

[0071] The heat treatment process for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment is the same as that in Embodiment 1, except that only Pr is added as a rare earth element.

[0072] The yield strength of the alloy was measured to be 913.4 MPa, the tensile strength was 1023.9 ​​MPa, and the elongation was 12.5%.

[0073] By comparison, it can be seen that the Pr element significantly reduces the yield strength of the alloy. The reason is that the addition of the Pr element alone may lead to the formation of some unfavorable precipitation phases.

[0074] Comparative Example 5

[0075] The heat treatment process for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment is the same as that in embodiment 1, except that: the rare earth element is only Yb

[0076] The yield strength of the alloy was measured to be 946.2 MPa, the tensile strength was 984.1 MPa, and the elongation was 11.2%.

[0077] By comparison, it can be seen that the effect of Yb element on improving the plasticity and toughness of the alloy is weak. The reason is that Yb element can prolong the aging response time of the alloy. As the aging time increases, the elongation of the material will decrease and the material will be more prone to fracture.

[0078] Comparative Example 6

[0079] The heat treatment process for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate described in this embodiment is the same as that in embodiment 1, except that the asynchronous cold rolling process is changed to ordinary cold rolling.

[0080] The yield strength of the alloy was measured to be 947.2 MPa, the tensile strength was 992.4 MPa, and the elongation was 7.8%.

[0081] By comparison, it can be seen that the elongation of ordinary cold rolling is lower than that of asynchronous cold rolling. The reason is that in ordinary cold rolling, the roller speed is the same, which may lead to higher rolling pressure. During the cold rolling process, the metal grains are elongated along the rolling direction to form a fibrous structure, which causes the metal properties to be directional. This makes the deformation texture unfavorable for the uniform distribution of plastic deformation, and greatly reduces the elongation of the material.

[0082] Table 4 Mechanical properties and corrosion test ratings of high strength corrosion resistant titanium alloys according to specific embodiments of the present invention

[0083]

[0084] In summary, the addition of a single rare earth element has little effect on the strength and corrosion resistance of the alloy, but the simultaneous addition of different rare earth elements can produce a synergistic effect in the titanium alloy, acting together on the microstructure and mechanical properties of the alloy; the combination of Pr and Yb can refine the grains and improve the strength and toughness of the alloy, while the combination of Ce and La can combine with oxygen to form stable oxides, reduce oxidation in the alloy, and improve the corrosion resistance of the alloy. The co-addition of La, Ce and Yb rare earth elements can more effectively consume harmful solute atoms, thereby reducing grain boundary embrittlement and improving the strength of the alloy.

[0085] Although conventional solid solution aging treatment can improve the strength and corrosion resistance of the alloy, the improvement effect is limited. In the present invention, through multi-stage solid solution aging treatment, rare earth elements can be better stimulated to improve the interface bonding strength between the precipitated phase and the matrix titanium, and the combination of Ce, Pr and Yb can more effectively enhance this interface bonding, thereby improving the strength and toughness of the alloy; since the added rare earth elements usually have a low solid solubility in the alloy, they tend to form compounds or aggregate near the grain boundaries; the co-addition of multiple rare earth elements may more effectively consume harmful solute atoms, thereby reducing grain boundary embrittlement and greatly improving the strength of the alloy.

[0086] The high-strength, corrosion-resistant titanium alloy described in the present invention is prepared by adding these four rare earth elements simultaneously to form a high-density multi-level dislocation structure, so that the solute atoms are evenly distributed, the bonding strength between the precipitated phase and the matrix is ​​improved, and the strength and corrosion resistance of the plate are greatly improved, thereby obtaining a titanium alloy that meets the performance requirements.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-strength, corrosion-resistant, fine-grained titanium alloy plate, characterized in that: The strength and corrosion resistance of the material are improved by adding rare earth elements lanthanum, cerium, praseodymium and ytterbium to the TC4 titanium alloy, combined with asynchronous cold rolling and solution treatment, which specifically includes the following steps: (1) Gas atomization treatment: The prepared rare earth raw materials and TC4 alloy raw materials are mixed by inert gas atomization treatment respectively; (2) sequentially subjecting the prepared titanium alloy powder to pressing and sintering, pre-annealing, asynchronous cold rolling, multi-stage solution treatment, and quenching; (3) The samples were then artificially aged at a temperature of 400-420°C for 4 h and then air-cooled to room temperature.

2. The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy sheet according to claim 1, characterized in that: The titanium alloy composition comprises 5.5-6.5% Al, 3.7-4.2% V, 0.8-1.2% La, 0.03-0.05% Ce, 0.02-0.04% Pr, 0.01-0.02% Yb, and the remainder is Ti and some inevitable impurity elements.

3. The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy sheet according to claim 1, characterized in that: The conditions for the gas atomization treatment are that the induction power reaches 60kW and the atomization gas pressure is 6.0MPa.

4. The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy sheet according to claim 1, characterized in that: The conditions for pressing and sintering are: sintering temperature is 1150-1300°C and time is 2h.

5. The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy sheet according to claim 1, characterized in that: The parameters of the pre-annealing treatment are: 300-350°C for 2h.

6. The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy sheet according to claim 1, characterized in that: The conditions of the asynchronous cold rolling treatment are: the total pressing amount of the sample is 50%, the pressing times are 10 times, and the pressing amount each time is not less than 5%.

7. The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate according to claim 1, characterized in that: A multi-stage solution treatment was carried out, with the first stage solution temperature being 850°C and the insulation time being 2 hours; the second stage solution temperature being 900°C and the insulation time being 2 hours; the third stage solution temperature being 950°C and the insulation time being 2 hours.

8. The method for preparing the high-strength, corrosion-resistant, fine-grained titanium alloy plate according to claim 1, characterized in that: During the artificial aging treatment in step (5), the aging temperature is 400-420° C. and the insulation time is 4 hours.

Citation Information

Patent Citations

  • Novel high-strength corrosion-resistant titanium alloy and preparation method thereof

    CN118291810A

  • Process method for improving surface strength and corrosion resistance of metal material

    CN118531342A

  • Heat treatment method for strong-strength titanium alloy

    CN103667790A

  • Thermal treatment method capable of improving performances of isotropic ultra-strong corrosion-resistant aluminum alloy rolled plate

    CN107475649A

  • Preparation method of high-strength and high-conductivity rare earth copper-nickel-silicon-chromium alloy

    CN109182795A

Cited By

  • Preparation method of high-toughness rare earth-containing titanium alloy bar

    CN122038822A